Mechanism investigation and process monitoring of electrical discharge machining - Xiao, Zhiyun (2008)
To improve process performance, better understanding of the discharge mechanism and the relationships among process performance, discharging conditions, and working parameters is aimed in this research. Studies started by investigating discharge mechanism to understand what is happening during an individual discharge.